2014
DOI: 10.4274/tjh.2012.0197
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the IL-5 Gene is Associated with Inhibitor Development in Severe Hemophilia A Patients

Abstract: Objective: A severe complication in the replacement therapy of hemophilia A (HA) patients is the development of alloantibodies (inhibitors) against factor VIII, which neutralizes the substituted factor. The primary genetic risk factors influencing the development of inhibitors are F8 gene mutations. Interleukins and cytokines that are involved in the regulation of B-lymphocyte development are other possible targets as genetic risk factors. This study assesses the possible involvement of 9 selected single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…hapmap.org and http:www.ncbi.nlm.nih.govsnp). Although the allele frequencies of IL-10 promoter polymorphisms found in healthy controls in our study were different from the prevalence rates reported in different regions of the The dendrogram demonstrates the nature of the interactions between polymorphisms There was a synergistic interaction, with the strongest interaction between the IL-10 (−1082 G/A) and (−592 C/A) polymorphisms world, they were similar to some previous studies performed in Turkish population [35,36]. These discrepancies in the minor allele frequencies of IL-10 promoter polymorphisms between healthy individuals demonstrated the importance of both ethnic and geographic diversity and sample size to evaluate study results in the genetic association studies [37].…”
Section: Discussionsupporting
confidence: 80%
“…hapmap.org and http:www.ncbi.nlm.nih.govsnp). Although the allele frequencies of IL-10 promoter polymorphisms found in healthy controls in our study were different from the prevalence rates reported in different regions of the The dendrogram demonstrates the nature of the interactions between polymorphisms There was a synergistic interaction, with the strongest interaction between the IL-10 (−1082 G/A) and (−592 C/A) polymorphisms world, they were similar to some previous studies performed in Turkish population [35,36]. These discrepancies in the minor allele frequencies of IL-10 promoter polymorphisms between healthy individuals demonstrated the importance of both ethnic and geographic diversity and sample size to evaluate study results in the genetic association studies [37].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, DNA sequence analysis of the IL-10 gene's promoter in patients with SP revealed 32% of position -1082 guanine into adenine (c. Despite the fact that the global prevalence notified of the allele frequencies of -1082, -819, and -592 SNPs in IL-10 gene in control groups vary, and they are same to last studies in Turkish society [13,21,22].…”
Section: Discussionsupporting
confidence: 56%
“…In this study, the IL-10 gene SNPs -1082, -819, -592 and their genotypic combinations in 100 SP patients and 100 volunteer-healthy controls in the Turkish population were Wide variation has been also recorded in the frequencies of IL-10 gene's promoter SNPs among distinct populations. Despite the fact that the global prevalence notified of the allele frequencies of -1082, -819, and -592 SNPs in IL-10 gene in control groups vary, and they are same to last studies in Turkish society [13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…These are summarized in Table 1. [40][41][42][43][44][45][46][47][48][49][50][51][52] Based on current understanding, it seems unlikely that a single marker of significantly greater importance than multiple others will be identified. In fact, the associations found between polymorphic genes and inhibitory antibodies have not been consistent across study cohorts, and the question, of course, is why?…”
Section: Immune Response Genesmentioning
confidence: 99%